Fc-fusion technology and recombinant FVIII and FIX in the management of the hemophilias - Mancuso ME; Mannucci PM (Dove Medical Press, 2014)
Maria Elisa Mancuso,1 Pier Mannuccio Mannucci21Angelo Bianchi Bonomi Hemophilia and Thrombosis Center, 2Scientific Direction, Fondazione IRCCS Ca' Granda, Ospedale Maggiore Policlinico, Milan, ItalyAbstract: Prophylaxis with regular infusions of factor VIII (FVIII)- or factor IX (FIX)- containing products is the mainstay of modern hemophilia care. However, this therapeutic regimen is inconvenient, requiring repeated intravenous injections from childhood. Approaches meant to prolong the half-life of FVIII and FIX in plasma have been developed in order to improve the feasibility and acceptability of replacement therapy, extending protection from bleeding, reducing infusion frequency and hence the need for venous access devices in young children. Several strategies have been implemented to enhance the pharmacokinetics of clotting factors, including conjugation with polyethylene glycol and the production by genetic engineering of fusion proteins containing the coagulation factors linked to a long-lived plasma protein such as albumin or the Fc fragment of immunoglobulin (Ig)G. The latter technology is one of the most promising, since the prolongation of FVIII and FIX half-life is obtained by exploiting the physiological binding of the Fc domain to the neonatal Fc receptor. Fc fusion monomers have been obtained with both recombinant FVIII (rFVIIIFc) and FIX (rFIXFc), and data from preclinical and clinical studies showed improved pharmacokinetics for both factors, which are produced in human embryonic kidney (HEK) 293 cells, thus ensuring full human post-translational modifications. In Phase I/IIa studies, rFVIIIFc and rFIXFc showed 1.5–1.7 fold and 3.0–4.0 fold longer elimination half-life, respectively. Similar data have been obtained in the Phase III clinical studies with rFVIIIFc and rFIX-Fc published recently. Both drugs were satisfactorily safe, particularly with respect to immunogenicity, and no serious adverse event was observed.Keywords: factor VIII, factor IX, long-acting molecules